Correlation of Immunomodulatory Cytokines with Tumor Volume and Cerebrospinal Fluid in Vestibular Schwannoma Patients - Becker, Anna Louisa; Scholle, Leila; Klause, Clara Helene; Staege, Martin Sebastian; Strauss, Christian; Otto, Markus; Rampp, Stefan; Scheller, Christian; Leisz, Sandra (Cancers, 2024)
Sporadic vestibular schwannomas (VSs) often exhibit slow or negligible growth. Nevertheless, some VSs increase significantly in volume within a few months or grow continuously. Recent evidence indicates a role of inflammation in promoting VS growth. Therefore, our study aimed to identify cytokines, which are associated with larger VSs. The expression of different cytokines in VS tumor samples and VS primary cultures was investigated. Additionally, the concentration of cytokines in cell culture supernatants of VS primary cultures and cerebrospinal fluid (CSF) of VS patients and healthy controls were determined. Correlation analysis of cytokine levels with tumor volume, growth rate, Koos grade, age, and hearing was examined with Spearman’s-rank test. The mRNA expression of CC-chemokine ligand (CCL) 18, growth differentiation factor (GDF) 15, and interferon regulatory factor 4 correlated positively with tumor volume. Moreover, the amount of GDF15 in the cell culture supernatant of primary cells correlated positively with tumor volume. The concentrations of the cytokines CCL2, CCL5, and CCL18 and transforming growth factor beta (TGFB) 1 in the CSF of the patients were significantly different from those in the CSF controls. Inhibition of immune cell infiltration could be a putative approach to prevent and control VS growth.
CRIS-Team Scopus Importer:2024-09-27
Keywords: acoustic neuroma; CC-chemokine ligand; cytokines; growth differentiation factor; transforming growth factor; tumor-associated macrophages; vestibular schwannoma